(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In the modern world, intellectual activity and the effective use of its results play a crucial role in the development of states and societies. They contribute to the emergence and rapid development of new industries and services, leading to qualitative changes across the entire social sphere. The transformation of the lifestyle and thinking style of youth significantly impacts intellectual potential, which is a key factor in progress across various areas of life.